In Vitro Comparative Study on Antiherpetic Effect of Chlorhexidine and Persica Mouthwashes with Acyclovir - Sara Pourshahidi; Fahimeh Rezazadeh; Mohammad Motamedifar; Mahdi Davarmanesh; Hooman Ebrahimi; Abbas Alipour (Journal of Basic & Applied Sciences, 2021)
Introduction: Recurrent intraoral herpes in one of the common oral diseases that causes painful ulcers and viral shedding. The question was if chlorhexidine and persica mouthwashes has antiviral effects comparing to acyclovir. Materials and Methods: In this experimental study, virucidal effects of both mouthwashes were examined, before and after HSV-1 infection of the vero cells, in the presence of various concentrations (½,¼,¹/8) of mouthwashes applied at different time intervals(0.5,1,5 minutes), by using quantal assays then were compared with acyclovir. The data were analyzed by one way and two way ANOVA. Results: Before inoculation, both mouthwashes showed virucidal effects on HSV-1, at all concentrations and persica showed more virucidal effect than chlorhexidine and acyclovir (p=0.0001,p= 0.04, respectively). After virus inoculation although persica and chlorhexidine indicated antiviral effect, this already were so far less than that of acyclovir which caused more significant reduction on virus titer (p=0.0001). Conclusion: Because of the better direct anti-HSV effect of the herbal mouthwash, persica, and its less side effects than chlorhexidine, it can be used for reduction of oral fluid contamination caused by viral shedding and also reduction of infectivity of oral ulcers.